Implementation of the Logistics Policy for the Regent and Deputy Regent of East Bolaang Mongondow Election in 2020 during the Covid 19 Pandemic - Worotitjan, Charles; Bogar, Wilson; Tumbel, Goinpeace Handerson; Mandagi, Marthinus (Technium Social Sciences Journal, 2022)
Public policy is a branch of science developing rapidly according to the community’s needs. Especially in the public sector and is a multidisciplinary branch of study that requires contributions from other sciences in everyday reality. Destination study this to describe, explain the factors Implementation of the Logistics Policy for the Election of Regent and Deputy Regent of Bolaang Mongondow Timur in 2020 during the Covid- 19 Pandemic. Researchers use qualitative research because they are interested in describing reality. The empirical background behind the phenomenon in-depth, detail, and thoroughness are related to the Implementation of the Logistics Policy for the Election of the Regent and Deputy Regent of East Bolaang Mongondow in 2020.Primary data sources were obtained from the field by observing or interviewing. Researchers use this data to get direct information about the Implementation of Logistics Policies for the Election of Regents and Deputy East Bolaang Mongondow Regent in 2020 to the Commissioner in charge of Logistics and the Officer or Implementer in charge of/in order of Election Logistics. Data sources are data obtained from reading sources and various other sources consisting of letters, reports, and official documents. In qualitative research, data collection is carried out in natural settings (natural conditions). Primary data sources and data collection techniques focus on observation, interviews, documentation. Analysis has started since formulating explaining the problem before going into the field and continues until the writing of the research results. Data analysis becomes a guide for further research until, if possible, a "grounded" theory. However, data analysis focuses more on qualitative research during the field process and data collection. The East Bolaang Mongondow KPU’s Logistics Management Team, as a policymaker, has carried out a detailed calculation of the logistics needs and election cable ties. Communication: the East Bolaang Mongondow Regency KPU with the District Election Committee and the Voting Committee has been well. Still, there is no exceptional socialization/ guidance regarding the needs and use of Election Logistics to KPPS. There is no socialization/ guidance on the condition and use of Election Logistics in stages starting from Regency KPU to PPK, then PPK to PPS, and PPS to KPPS. There is no budget arrangement for socialization/ guidance of technology regarding the need and use of Election Logistics.